The nature of newspaper coverage of homicide. Issue 2 (1st June 2002) - Taylor, C A; Sorenson, S B
Abstract : Objectives: Previous research has shown that some homicides are more likely than others to receive newspaper coverage (for example, homicides by strangers). The present investigation examined whether, once the decision has been made to report on a homicide, the nature of the coverage (that is, how much visibility is given to a story, what information is included, and how a story is written) differs according to two key variables, victim ethnicity, and victim-suspect relationship. Setting: Los Angeles, California (USA). Methods: Homicide articles from the 1990–94 issues of the Los Angeles Times were stratified according to the predictors of interest (victim ethnicity and victim-suspect relationship) and a sample was drawn. Data that characterized two primary aspects of newspaper coverage, prominence and story framing (including background information, story focus, use of opinions, story tone, and "hook" or leading introductory lines) were abstracted from the articles. Descriptive statistics and cross tabulations were generated. Multivariate analyses were conducted to examine the predictive value of victim ethnicity and victim-suspect relationship on the nature of the newspaper coverage. Results: Newspaper coverage of homicide was generally factual, episodic, and unemotional in tone. Victim-suspect relationship, but not victim ethnicity, was related to how a story was covered, particularly the story frame. Homicides by intimates were covered consistently differently from other types of homicides; these stories were less likely to be opinion dominated, be emotional, and begin with a "hook". Conclusion: Victim-suspect relationship was related to the nature of coverage of homicides in a large, metropolitan newspaper. Given the agenda setting and issue framing functions of the news media, these findings have implications for the manner in which the public and policy makers perceive homicides and, consequently, for the support afforded to various types of solutions for addressing and preventing violence.